MSME AWARENESS OF ISLAMIC PROFIT AND LOSS SHARING IN BRUNEI DARUSSALAM - RUVIMBO NJAWAYA; PG MD HASNOL ALWEE PG HJ MD SALLEH (Journal of Business & Economic Analysis, 2023)
In Islamic finance, Profit and Loss Sharing (PLS) concepts are widely advocated as one of the most equitable concepts available for Islamic Financial Institutions (IFIs), given the equitable nature of sharing one’s profit and loss. However, in practice its use is limited as challenges exist which include moral hazard and a mismatch of the competencies of contemporary IFIs vis-a-vis the risk profile of PLS concepts. These challenges of PLS from an IFI perspective had been extensively covered in the literature, therefore this paper attempts to assess the challenges of PLS from a consumer or demand perspective. It is argued that there should be a reasonable level of awareness and willingness for consumers to demand a particular product; it is economically inefficient to create a product for which demand is lacking. Using a mixed method research design which includes surveys to 177 MSMEs and semi-structured interviews with two Islamic finance academicians, the findings indicate a low-level awareness of Mudarabah and Musharakah amongst MSMEs. Further, the willingness to use PLS financing among MSMEs is also found to be low, notably in terms of the willingness to share profits with IFIs, as well as having reservations on IFIs to be involved in playing an operational role in the small enterprise. These findings prompt the need for enhanced marketing approaches to enhance the awareness of these concepts for MSMES, and at the same time, defining a selective target market to explore the willingness amongst MSMEs, should PLS financing be widely available in Brunei.